2017
DOI: 10.1590/s1677-5538.ibju.2015.0132
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of EGF and MCP-1 in children with vesico-ureteral reflux

Abstract: Purpose The aim of this study was to investigate the urinary concentration of epidermal growth factor (EGF) and monocyte chemotactic protein-1 (MCP-1) as reflux nephropathy (RN) biomarkers before and after endoscopic treatment of moderate to severe vesico-ureteral reflux (VUR).Materials and methods A prospective study was carried out on 72 children with moderate to severe VUR. All patients underwent endoscopic treatment using Macroplastique® or Deflux®. Vesico-ureteral reflux resolution was tested by post-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…15 Furthermore, it has been demonstrated that EGF, MCP-1 (plus their ratio EGF/MCP-1), and β2M may be used as possible indicators of progressive renal damage and recovery in children with urinary tract obstruction 3,6,16 and VUR. 17 Similar findings in obstructive nephropathy patients have been observed by other authors. 18 The separate monitoring of these urinary biomarkers may not be indicative of an ongoing process occurring in renal parenchyma, 19 which is most likely influenced by the interaction of MCP-1 and EGF so we studied also uEGF/uMCP-1 and uEGF/u β2M ratios.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…15 Furthermore, it has been demonstrated that EGF, MCP-1 (plus their ratio EGF/MCP-1), and β2M may be used as possible indicators of progressive renal damage and recovery in children with urinary tract obstruction 3,6,16 and VUR. 17 Similar findings in obstructive nephropathy patients have been observed by other authors. 18 The separate monitoring of these urinary biomarkers may not be indicative of an ongoing process occurring in renal parenchyma, 19 which is most likely influenced by the interaction of MCP-1 and EGF so we studied also uEGF/uMCP-1 and uEGF/u β2M ratios.…”
Section: Discussionsupporting
confidence: 85%
“…We have shown that urinary tract obstruction and VUR are associated with increased urinary excretion of MCP-1. [6][7][8]17 Then, the presence of associated conditions such as urinary tract obstruction and vesicoureteral in hypoplastic, agenetic, and multicystic groups justified itself the increased urine excretion of MCP-1/Creat in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar assay results were found in other studies having higher levels of MCP1 in pediatric obstructive uropathy and reflux nephropathy. [ 14 15 16 ]…”
Section: R Esult and Discussionmentioning
confidence: 99%